Exploring the placement of gambling problems within the Hierarchical Taxonomy of Psychopathology - Carla Martí Valls; Anders Håkansson; Matti Cervin (PLoS ONE, 2025)
The placement of gambling problems within the Hierarchical Taxonomy of Psychopathology (HiTOP) framework, which organizes psychopathology alongside broad overarching symptom spectra, is unclear. With the objective to identify associations between gambling problems and the internalizing, externalizing, and thought disorder spectra of the HiTOP, we distributed an online survey to a sample of 1005 Swedish gamblers (52.4% men, aged 18 to 60 and older). Gambling problems were measured using the Problem Gambling Severity Index, and the main HiTOP spectra were assessed with brief versions of the Inventory of Depression and Anxiety Symptoms II, the Externalizing Spectrum Inventory, and the Thought Disorder Scale. Exploratory and confirmatory factor analysis showed that the brief HiTOP scales adequately captured the internalizing, externalizing, and thought disorder spectra. Within this structure, gambling problems emerged as a distinct factor significantly correlated with all three spectra and with unique associations with each: externalizing (β =  0.33, p < .001), thought disorder (β =  0.30, p = .001) and internalizing (β =  0.22, p = .022). In men, gambling problems were significantly associated with the thought disorder (β =  0.54, p < .001) and externalizing (β =  0.31, p < .001) spectra. In women, gambling problems were significantly associated with the externalizing (β =  0.39, p < .001) and internalizing (β =  0.35, p = .013) spectra. Our study is a first attempt to link gambling problems to the three main spectra of the HiTOP. Our findings show that gambling problems are associated with all three spectra and that there may be potential gender differences in the associations between gambling problems and co-occurring psychopathology.